Environmental issues, governmental policies, and accountability on the public communication agenda. Statistical results from Central and Eastern European countries - Grecu, Silviu-Petru; Chiriac, Horia-Costin (Technium Social Sciences Journal, 2023)
This paper highlights the importance of environmental policies in a social and economic context characterized by multiple structural crises. The beginning of the XXI-st century proposes a new perspective, based on the transition from industrial to clean energy and green economies. In this context, environmental preservation should be seen as a main goal for decision-makers and the civic community. The paper aims to identify several relevant predictors that are involved in the further dynamics of the Environmental Performance Index. In order to argue the role played by economic factors in preserving the environment, the paper used quantitative and multivariate statistics, being based on linear, nonlinear, and multiple equations of regression. Using one-way ANOVA and nearest neighbourhood methods, the paper highlights the fact that environmental performance is strongly related to economic welfare, governmental coordination of climate policies, the level of sustainable development, and civic accountability.